The Graz Liver Allocation Strategy—Impact of Extended Criteria Grafts on Outcome Considering Immunological Aspects - Kahn, Judith; Pregartner, Gudrun; Avian, Alexander; Kniepeiss, Daniela; Müller, Helmut; Schemmer, Peter (Frontiers in Immunology, 2020)
Background. Transplant centers are forced to use livers of extended criteria donors for transplantation due to a dramatic organ shortage. The outcome effect of extended donor criteria (EDCs) remains unclear. Thus, this study was designed to assess the impact of EDCs on outcome including immunological aspects after liver transplantation (LT). Patients and Methods. Between November 2016 and March 2018 49 patients (85.7% male) with a mean age of 57+11 years underwent LT. The impact of EDCs on outcome after LT was assessed retrospectively using both MedOcs and ENIS (Eurotransplant Network Information System). Results. About 80% of grafts derived from extended criteria donors. Alanine aminotransferase/aspartate aminotransferase (AST/ALT) levels elevated more than three times above normal values in organ donors was the only significant risk factor for primary dysfunction (PDF) and primary non-function (PNF)/Re-LT and early non-anastomotic biliary strictures (NAS). Balance of risk (BAR) score did not differ between EDC and non-EDC recipients. PDF (14.3% of all patients) and PNF (6.1% of all patients) occurred in 23.1% of EDC-graft recipients and in 10.0% of non-EDC-graft recipients (RR 2.31, p<0.663). The 90-day mortality was 3.6%. There was no difference of early non-anastomotic biliary tract complications and biopsy proven rejections (BPR). There was no correlation of PDF/PNF with BPR and NAS respectively; however, 66.7% of the patients with BPR also developed early NAS (p<0.001). Conclusion. With the Graz liver allocation strategy excellent survival can be achieved selecting livers with no more than 2 not outcome-relevant EDCs for patients with MELD >20. Further, BPR is associated with biliary complications.